Use of highly porous shell and variable-angle locking screws for acetabular revision surgery: our experience and medium term results - Ambrosini, Jacopo; Giaretta, Stefano; Vicenti, Giovanni; Zocca, Claudia; Buono, Claudio; Spolettini, Pietro; Solarino, Giuseppe; Momoli, Alberto (Lo Scalpello - Journal, 2025)
This article presents the clinical outcomes and experiences of our hospital in utilizing highly porous shells with variable-angle locking screws in acetabular revision surgery in patients with total hip arthroplasty (THA). A retrospective analysis was conducted on 16 acetabular revision cases, and patients were followed for an average of 22 months. The postoperative functional outcomes were evaluated with the Harris Hip Score (HHS) and Western Ontario and McMaster Universities Arthritis Index (WOMAC). Complications and radiographic findings were also analyzed. The results demonstrate promising outcomes with improved hip function, pain relief, minimal complications and implant stability. Our findings contribute to the growing evidence supporting the efficacy and safety of high porosity cotyles in revision surgery of THA.